Penerapan Media Sensory Play dalam Menstimulus Kemampuan Motorik Halus Anak Usia 5-6 Tahun di TK Tunas Kasih Makassar - Suharti; Sitti Nurhidayah IIyas; Azizah Amal (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research examines the application of sensory play media in stimulating the fine motor skills of children aged 5-6 years at Tunas Kasih Kindergarten, Makassar. The research focus in this study is how to apply sensory play media to stimulate the fine motor skills of children aged 5-6 years at Tunas kasih Kindergarten, Makassar. The aim of this research is to find out how the application of sensory play media can stimulate the fine motor skills of children aged 5-6 years at the Tunas Kasih Kindergarten, Makassar. The approach used in this research is a qualitative research approach. The type of research used in this research is descriptive qualitative. The research subjects used in this research were class teachers and class B students at Tunas Kasih Kindergarten, Makassar. The object of this research was the application of sensory play media in stimulating children’s fine motor skills at Tuna Kasih Kindergarten, Makassar. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data reducation, data presentation and drawing conclusions. The results of the research show that Tunas Kasih Kindergarten, Makassar uses sensory play media to stimulate children’s fine motor skills, namely by using kinetic sand media and plasticine media which is done twice a week.